The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Proceedings of the 13th ACM Conference on Recommender Systems 2019
DOI: 10.1145/3298689.3347058
|View full text |Cite
|
Sign up to set email alerts
|

Are we really making much progress? A worrying analysis of recent neural recommendation approaches

Abstract: Deep learning techniques have become the method of choice for researchers working on algorithmic aspects of recommender systems. With the strongly increased interest in machine learning in general, it has, as a result, become difficult to keep track of what represents the state-of-the-art at the moment, e.g., for top-n recommendation tasks. At the same time, several recent publications point out problems in today's research practice in applied machine learning, e.g., in terms of the reproducibility of the resu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
166
1
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 413 publications
(217 citation statements)
references
References 50 publications
13
166
1
5
Order By: Relevance
“…We do not use Neural Collaborative Filtering [11] or Bayesian Personalized Ranking (BPR) [17] as baselines, as their accuracies were found to be so low on these data-sets that no results were reported in [14], see also [5]. We compare these baselines to the following variants of the ADMM-approach outlined in Section 3:…”
Section: Methodsmentioning
confidence: 99%
“…We do not use Neural Collaborative Filtering [11] or Bayesian Personalized Ranking (BPR) [17] as baselines, as their accuracies were found to be so low on these data-sets that no results were reported in [14], see also [5]. We compare these baselines to the following variants of the ADMM-approach outlined in Section 3:…”
Section: Methodsmentioning
confidence: 99%
“…It is worthwhile noting that deep learning (DL) models for personalized recommendation have emerged in recent years. We acknowledge that whether DL models truly improve the recommendation performance is controversial (Dacrema et al, 2019), but this problem is out of the scope of this survey. In this survey, we will focus on the problem that the black-box nature of deep models brings difficulty in model explainability.…”
Section: A Historical Overviewmentioning
confidence: 99%
“…This is not ideal, as usually the approach's implementation as well as additional information is needed to facilitate reproducing the experiment and results. For example, in [6], it is reported that only 7 out of 18 major neural recommendation approaches published at top tier conferences were reproducible, as only limited information was shared by the authors. Following the PRIMAD model [4,7] would resemble a large step towards reproducibility.…”
Section: Requirementsmentioning
confidence: 99%
“…BioASQ. The challenge on biomedical semantic indexing and question answering (BioASQ) [27] aims to improve the indexing process of PubMed 6 articles with the annotation of terms from the Medical Subject Headings (MeSH) 7 . In 2013, the BioASQ challenge was initiated in cooperation with the National Library of Medicine (NLM).…”
Section: Evaluation Infrastructuresmentioning
confidence: 99%